2019
DOI: 10.3390/w11061278
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Behavior of Uranium and Radon in Groundwater of Jurassic Granite Area, Icheon, Middle Korea

Abstract: Uranium concentrations (a total of 82 samples) in groundwater in Icheon, middle Korea, showed a wide range from 0.02 to 1640 μg/L with a mean of 56.77 μg/L, a median of 3.03 μg/L, and a standard deviation of 228.63 μg/L. Most groundwater samples had quite low concentrations: 32.9% were below 1 μg/L, while 15.9% exceeded 30 μg/L, the maximum contaminant level (MCL) of the US EPA (Environmental Protection Agency). Radon concentrations also ranged widely from 1.48 to 865.8 Bq/L. Although the standard deviation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Leachate may occur in POM. This is observed from the piper plot by the formation of the mixed type of cations and anions Ca-Na-HCO 3 are distinctive of granite aquifer with feldspars (Cho and Choo 2019) and also Ca-Cl (Chidambaram et al 2012).…”
Section: Hydrogeochemical Processesmentioning
confidence: 84%
See 1 more Smart Citation
“…Leachate may occur in POM. This is observed from the piper plot by the formation of the mixed type of cations and anions Ca-Na-HCO 3 are distinctive of granite aquifer with feldspars (Cho and Choo 2019) and also Ca-Cl (Chidambaram et al 2012).…”
Section: Hydrogeochemical Processesmentioning
confidence: 84%
“…The solubility of radionuclides governs the distribution and dispersion in water (Jordana and Batista 2004). Studies have reported U level in groundwater used for drinking purpose (De Camargo and Mazzilli 1996;Chau and Michalec, 2009;Killiari and Pashalidis 2010;Thivya et al 2015aThivya et al , 2015bBrindha et al 2011a, b;Cho and Choo 2019). The studies have also tried to trace the geochemical processes behind the release of U in groundwater (Mahalakshmi et al 2017, Paramaguru et al 2016Chandramohan et al 2018;Adithya et al 2019Adithya et al , 2020Selvi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The statistical method such as multivariate analysis can be used to characterize its geochemical processes through data reduction and classification with respect to chemical composition of groundwater. When correlation analysis and factor analysis are applied to chemical data of groundwater, dominant processes can be identified as common factors that are sets of variables having strong associations with one another [33][34][35][36][37].…”
Section: Correlation Analysis and Factor Analysismentioning
confidence: 99%
“…The use of the U isotopic composition has been proven to be very valuable for studying different physicochemical processes in estuarine water [8], seawater [9,10], and continental surface water and groundwater [11][12][13][14]. U isotopes in continental waters can be investigated as a tracing or dating tool for a broad spectrum of hydrological and geological processes [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, not much is known about freshwater draining areas with a predominantly carbonate lithology. In such hydrogeological settings, these isotopes have much lower concentrations of 0.02-21.4 µg/L (mean: 0.3 µg/L) [12,13,34], which is analytically challenging. Recently, multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS) has been used to improve precision because it affords high absolute sensitivity and simultaneous detection of ions compared with quadrupole-based ICP-MS and achieves a higher sample throughput compared with thermal ionization mass spectrometry (TIMS).…”
Section: Introductionmentioning
confidence: 99%